2013
DOI: 10.1097/rlu.0b013e318266d4bd
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Metastases of Rectum From Carcinosarcoma (Malignant Müllerian Mixed Tumor) of Uterine Cervix

Abstract: A 25-year-old woman had carcinosarcoma of uterine cervix after definitive treatment. One year later, local recurrent disease was found in the right posterior pelvis on FDG PET/CT. FDG PET/CT also disclosed an incidental intramural hypermetabolic lesion in the rectum, which seemed separate from the right pelvic lesion on contrast-enhanced CT. The rectal lesion was confirmed as metastatic carcinosarcoma from uterine cervix after endoscopic biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Carcinosarcoma usually occurs in postmenopausal women; the incidence of carcinosarcoma in premenopausal women is exceedingly rare. A 25 years old woman with CCS has been reported [ 4 – 6 ]. The typical clinical symptoms are vaginal bleeding; other symptoms include vaginal discharge, abdominal mass, abdominal pain, or no obvious symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinosarcoma usually occurs in postmenopausal women; the incidence of carcinosarcoma in premenopausal women is exceedingly rare. A 25 years old woman with CCS has been reported [ 4 – 6 ]. The typical clinical symptoms are vaginal bleeding; other symptoms include vaginal discharge, abdominal mass, abdominal pain, or no obvious symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ovarian carcinosarcoma [ 5 ], the majority of UCS and CCS are at an early stage without peritoneal metastasis. However, even though carcinosarcoma is in stage I, the 5-year survival rate is still less than 50% [ 6 ]. It was previously reported that invasion depth and clinical stage were independent risk factors for prognosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]31,33 F-FDG PET/CT scans performed in 12 previous studies (Table 3). The various anatomical sites were the uterus (six studies, median SUVmax: 10.13), 25,[46][47][48][49][50] prostate (one study, SUVmax: 9.70), 23 liver (one study, SUVmax: 17.10), 24 stomach (one study, SUVmax: 11.90), 51 pulmonary system (two studies, median SUVmax: 10.47), 52,53 and hypopharynx (one study, SUVmax: 8.06). 15 Furthermore, the median SUVmax of all of these studies was 11.23, similar to the value of 10.30 reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…26,29,31 PET-CT is sometimes available to assure extrauterine metastasis in patients with CCS. 11,32,33 The gold standard of diagnosing CCS is pathological examination. As the accessibility of the uterine cervix, cervical biopsy examination is easy performed and can bring a definite diagnosis of CCS.…”
Section: Diagnosismentioning
confidence: 99%
“… 26 , 29 , 31 PET-CT is sometimes available to assure extrauterine metastasis in patients with CCS. 11 , 32 , 33 …”
Section: Diagnosismentioning
confidence: 99%